2017
DOI: 10.1007/s00395-017-0635-0
|View full text |Cite|
|
Sign up to set email alerts
|

Differential regulation of protein phosphatase 1 (PP1) isoforms in human heart failure and atrial fibrillation

Abstract: Protein phosphatase 1 (PP1) is a key regulator of important cardiac signaling pathways. Dysregulation of PP1 has been heavily implicated in cardiac dysfunctions. Accordingly, pharmacological targeting of PP1 activity is considered for therapeutic intervention in human cardiomyopathies. Recent evidence from animal models implicated previously unrecognized, isoform-specific activities of PP1 in the healthy and diseased heart. Therefore, this study examined the expression of the distinct PP1 isoforms PP1α, β, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Interestingly, β‐adrenergic receptor blocking therapy was associated with lower PP‐1 abundance and activity in human failing ventricles, suggesting phosphatases rather than kinases as possible targets for the treatment of some human cardiac diseases (Meyer‐Roxlau et al . ). Furthermore, inhibition of RyR2 phosphorylation at S2808 was shown to exacerbate cardiac dysfunction in a model of Ca 2+ ‐dependent cardiomyopathy, suggesting a role for de‐phosphorylation of RyR2 in pathophysiological Ca 2+ handling (Liu et al .…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, β‐adrenergic receptor blocking therapy was associated with lower PP‐1 abundance and activity in human failing ventricles, suggesting phosphatases rather than kinases as possible targets for the treatment of some human cardiac diseases (Meyer‐Roxlau et al . ). Furthermore, inhibition of RyR2 phosphorylation at S2808 was shown to exacerbate cardiac dysfunction in a model of Ca 2+ ‐dependent cardiomyopathy, suggesting a role for de‐phosphorylation of RyR2 in pathophysiological Ca 2+ handling (Liu et al .…”
Section: Discussionmentioning
confidence: 97%
“…In line with above hypothesis, we observed reduced AF vulnerability and decreased AF duration post fish oil treatment, thus fish oil could attenuate electrical remodeling in this RAP-induced AF model. during AF [21][22][23][24]. ERS marker protein such as glucose-regulated protein78 (GRP78) was significantly increased in the tachypacing induced AF model and atrial myocardium obtained from AF patients [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…during AF [21][22][23][24]. ERS marker protein such as glucose-regulated protein78 (GRP78) was significantly increased in the tachypacing induced AF model and atrial myocardium obtained from AF patients [23,24]. UPR effectors like protein kinase R-like ER kinase (PERK) could destabilize voltage-gated cardiac Na + channel α-subunit (SCN5A) and Kv4.3 channel expression, which were important mediators of electric remodeling 22 .…”
Section: Discussionmentioning
confidence: 99%
“… 32 Moreover, since TJ is an actin-based cell junction type, a correspondence between ZO-1 alpha + and F-actin may indicate the influence of the spatial organizaiton of subsurface actin on alpha + or alpha − -involved TJ assembly/disassembly. 32 In human, the isoform-specific activities of protein phosphatase 1 (PP1) in heart failure and atrial fibrillation have been reported, 33 results proposed that isoform-specific targeting of PP1 α activity might be an innovative stragegy for human cardiac diseases but not PP1 β or PP1 γ . 33 …”
Section: Discussionmentioning
confidence: 99%
“… 32 In human, the isoform-specific activities of protein phosphatase 1 (PP1) in heart failure and atrial fibrillation have been reported, 33 results proposed that isoform-specific targeting of PP1 α activity might be an innovative stragegy for human cardiac diseases but not PP1 β or PP1 γ . 33 …”
Section: Discussionmentioning
confidence: 99%